The Role of Financial Inclusion and Digital Financial Literacy in Mediating the Influence of Financial Technology Use on Stock Investment Decisions - Baiq Nana Dwi Herdiana; Maretha Ika Prajawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Financial Technology (FinTech) usage on stock investment decisions among Generation Z users of the Stockbit application in Malang City, with financial inclusion and digital financial literacy as mediating variables. Using a quantitative approach and purposive sampling, 102 respondents were surveyed through an online questionnaire. The data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique with SmartPLS 3.0 software. This finding shows that FinTech usage has a positive but insignificant direct effect on stock investment decisions. However, FinTech significantly enhances financial inclusion and digital financial literacy, both of which positively influence investment decisions. These mediating variables strengthen the indirect relationship between FinTech usage and stock investment decisions. This study highlights the importance of digital financial literacy and inclusive access to formal financial services in optimizing fintech’s role in shaping rational investment behavior. Keywords: Financial Technology, Financial Inclusion, Digital Financial Literacy, Stock Investment Decision